Epigenome-wide association study of peripheral blood mononuclear cells in systemic lupus erythematosus: Identifying DNA methylation signatures associated with interferon-related genes based on ethnicity and SLEDAI - Joseph, Stancy; George, Nysia I.; Green-Knox, Bridgett; Treadwell, Edward L.; Word, Beverly; Yim, Sarah; Lyn-Cook, Beverly (Journal of autoimmunity, 2019)
Systemic lupus erythematosus (SLE or lupus) is a heterogeneous autoimmune disease characterized by the involvement of multiple organs and the production of antinuclear antibodies. DNA methylation plays an important role in the pathogenesis of lupus. We have performed an epigenome-wide DNA methylation study in lupus and healthy control (non-lupus) subjects to identify epigenetic patterns in lupus characterized ethnicity and SLE disease activity index (SLEDAI). A total of fifty-seven lupus patients (39 African American (AA) and 18 European American (EA)) and 33 healthy controls (17 AA and 16 EA) were studied. Differential DNA methylation between lupus patients and controls was assessed for approximately 485,000 CpG sites across the genome. We identified 41 differentially methylated sites (associated with 30 genes) between lupus and control s subjects, 85% of which were hypomethylated. Significant hypomethylation of differentially methylated sites was associated with several interferon-related genes, including MX1, IFI44L, PARP9, DT3XL, IFIT1, IFI44, RSAD2, PLSCR1, and IRF7. Several of these associated genes were also hypomethylated in comparisons between AA lupus and AA non-lupus subjects and between lupus patients with SLEDAI>6 and non-lupus subjects. Our analysis of gene expression data through RT-PCR confirmed these findings. Thus, the results indicate epigenetics susceptibility in lupus, which may be associated with SLEDAI score and ethnicity. In addition, our findings support the importance of the Type 1 interferon pathway in lupus pathogenesis. •Systemic lupus erythematosus is characterized by DNA methylation signature.•African Americans (AA) have a robust DNA methylation profile compared to European Americans (EA).•Patients with SLEDAI>6 scores have robust DNA methylation profile compared to patients with SLEDAI≤6 scores.•Interferon-related genes have a robust hypomethylation pattern in AA patients and patients with SLEDAI>6 score.